Malay Emigrants and Their Islamic Mission in South Sulawesi in 16th to 17th Century - Sulistyo, Bambang (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: The presence of Malay people in South Sulawesi indicated the beginning of its civilization development. They played an important role in economy, politics, and religion. The trade navigation grew, connecting South Sulawesi with other parts of the archipelago. Gowa kingdom, then Makassar, was for the first time agrarian community and eventually developed to be maritime area when Malay people were appointed as harbor masters. In sixteenth century, South Sulawesi had changed drastically and led to its culmination in seventeenth century. At this time, South Sulawesi was very dominant in political role in the archipelago and even it took over the roles which were previously played by the Western part of Indonesia. In this process, the role of Malay emigrants was very important, especially in developing civilization. Their strategies started in cultural development. In search of the early Islamization in South Sulawesi, it is not adequate to study the local condition only since Islam had developed in all over big civilized countries, such as Europe, Middle East, and Asia, included China. The navigation activities network had become global. The Islamic leadersâ authority at this time had been beyond the boundaries of the nations and even the continents. In addition to primary sources, this study also used mostly historiographical sources relating with Islamization in South Sulawesi.KEY WORDS: Malay people, emigrants, process of Islamization, Gowa kingdom, political role, developing civilization, and South Sulawesi.About the Author: Dr. Bambang Sulistyo is a Senior Lecturer at the History Department, Faculty of Humanities UNHAS (Hasanuddin University) in Makassar, South Sulawesi, Indonesia. For academic purposes, he can be reached at: bambang5ulistyo@yahoo.comHow to cite this article? Sulistyo, Bambang. (2014). âMalay Emigrants and Their Islamic Mission in South Sulawesi in 16th to 17th Centuryâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.53-66. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (September 4, 2014); Revised (October 10, 2014); and Published (October 28, 2014).